FB, THEY AND ME – THE ATTEMPTS OF USING SOCIAL MEDIA AS TOOLS FOR REFLECTIVE LEARNING AND COMMUNICATING AT THE UNIVERSITY - Bielinis, Lidia (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2017)
The concept of reflective learning focuses on the idea of analysing the practitioners’ experiences and the way they can learn from them. Considering the higher education, the author decided to describe students’ and academic teacher’s experiences related to learning and communicating through closed groups on Facebook. The three words: FB, they, me are deliberately put together in the title of this article. The experiences were collected to analyse the authors’ own teaching methods and to determine the best learning outcomes by academic teachers and students. The methods of collecting data were mainly based on individual, Internet interviews. As a theoretical concept, the author referred to reflective learning models introduced by (among others) D. A. Schön, T. Borton, D. A. Kolb and G. Gibbs as well as to the theory of transformative learning and Connectivism.